IMPLEMENTATION OF INDUSTRIAL SAFETY - Pratik Bhosale; Sushant Jagtap; Anantrao Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
In today’s world, technology has influenced human beings by various means in their life. Mainly the technology which is helpful in providing the safety as well as simple operation to thehuman being is known as automation. Nowadays, industrial safety is considered as an important factor and is implemented as per the risk assessment in various industries. Risk assessment is carried out using SIL & CAT level. Safeguarding the hazardous areawill usually involve the use of some kind of control system, and the Machinery Directive gives various requirements for the performance of the control system. In particular it states “Control system must be designed and constructed in such a way as to prevent hazardous situation from arising”. Various safety devices are available in market, which are useful in providing the safety for different operations.